2012
DOI: 10.1364/oe.20.013055
|View full text |Cite
|
Sign up to set email alerts
|

Exponentiated Weibull distribution family under aperture averaging for Gaussian beam waves

Abstract: Nowadays, the search for a distribution capable of modeling the probability density function (PDF) of irradiance data under all conditions of atmospheric turbulence in the presence of aperture averaging still continues. Here, a family of PDFs alternative to the widely accepted Log-Normal and Gamma-Gamma distributions is proposed to model the PDF of the received optical power in free-space optical communications, namely, the Weibull and the exponentiated Weibull (EW) distribution. Particularly, it is shown how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(90 citation statements)
references
References 28 publications
1
87
0
2
Order By: Relevance
“…Variable x equals NP M / t (P t denotes the average transmitted power) for signal time slot and zero for non-signal time slot. Here, h is the fading coefficient that features the power fluctuations, which can be modeled by the EW distribution with the below PDF [13] …”
Section: System Model and Ser Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Variable x equals NP M / t (P t denotes the average transmitted power) for signal time slot and zero for non-signal time slot. Here, h is the fading coefficient that features the power fluctuations, which can be modeled by the EW distribution with the below PDF [13] …”
Section: System Model and Ser Analysismentioning
confidence: 99%
“…Particularly, both of them have been used to study the effects of aperture averaging [7,12]. Recently, one novel fading model named exponentiated Weibull (EW) distribution was proposed by Ricardo Barrios and Federico Dios [13,14]. Their studies show that EW distribution fits more accurately with the actual PDF data than GG and LN distributions under all aperture averaging conditions and weak-to-strong turbulence regime [14].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, EW distribution is a novel one, which is proposed and experimentally verified by Barrios and Dios in Refs. [6,7]. Their study revealed that this distribution could model the PDF of irradiance in weak-to-strong turbulence regimes under all aperture-averaging conditions.…”
mentioning
confidence: 96%
“…The corresponding PDF and cumulative distribution function (CDF) of h a can be expressed as [6] f h a ðhÞ ¼ αβh…”
mentioning
confidence: 99%
See 1 more Smart Citation